PROFESIONALISME GURU DALAM PENGGUNAAN METODE DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR IPA DI KELAS IV SEKOLAH DASAR NEGERI 28 AIR TAWAR TIMUR KOTA PADANG - Syamsu Arlis (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
The purpose of this research is to improve the students learn of result in Natural Science through discovery approach of the IV grade students of Elementary School in Air Tawar, Padang. This research is a Classroom Action which consist of two meetings in two cycles. This research utilizes four steps of actions, are planning, action, observation, and reflection. The result of the study shows that the students learn of result in Natural Science experiencing of improvement and the improvement of students’ achievement can be observed from the affective, psychomotor, and cognitive.